Clima organizacional para empresas públicas y privadas (2017)
This document is the result of the consultation of the most representative authors who have studied and investigated an important and incident aspect, such as the organizational climate of public and private entities; for which there will be an initial contextualization about the organizations, the theoretical emergence of the different investigations related to the complexity, the historical connotations in the different eras, through the times. It will also deal with the influence of people within organizations and the relationship between the individual and the organization, aspects that will be of vital importance to address the central theme of the theoretical framework.